(untitled) (Ustozlar uchun, 2025)
This article explores the multifaceted roles of somatic objects in shaping the meaning, function, and reception of paramilogical texts. Using interdisciplinary approaches combining semiotics, phenomenology, and discourse analysis, the study presents a systematic investigation into how somatic objects mediate the interplay between embodied human experience and symbolic logic in these texts. Somatic objects, broadly defined as corporeal or bodily artifacts and representations, play a significant role in paramilogical texts, which are narrative or discursive constructs that blend logic, belief, and embodied experience.It argues that somatic objects are pivotal in grounding abstract paramilogical concepts in tangible, experiential realities, thus enriching interpretive possibilities.